Political compromise under conservative hegemony: Pezeshkian’s strategy in post-2024 Iran - Sidik Permana (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Masoud Pezeshkian’s victory in the 2024 Iranian elections ended the conservative group’s dominance of the executive branch. This study analyzes the challenges of bridging the gap between reformism and conservatism in Iran’s political system. This research uses a qualitative method with a literature study approach. The theory of party ideology and political compromise serves as its theoretical framework. The results show that Pezeshkian’s political compromise tends to be intersectional and conjunctional, avoiding potential conflict by ignoring controversial matters and integrating various conflicting principles, especially in ideological views. This pattern is reflected in his relations with conservative nationalists, particularly in managing relations with Iran’s Supreme Leader, Ayatollah Ali Khamenei, the Iranian Revolutionary Guards, and parliament. These findings suggest that political compromise serves as a pragmatic strategy for maintaining government stability, despite significant structural limitations. Theoretically, this study contributes to the development of compromise-diplomatic political strategy. Practically, this strategy can serve as a guideline for political actors in building and evaluating the political ecosystem in a religious-hybrid authoritarian state, such as Iran.